Studying the Relationship between Supply Chains and Achieving Competitive Advantage for Organizations (An Empirical Study on the Egyptian Poultry Sector) - El-Dabet, Abdallah Mohamed Hasan; El- Sayed, Khaled Kadry (The Arab Journal of Administration, 2025)
The study dealt with analyzing the role of the supply chain in achieving the competitive advantage of the organization by applying to the poultry sector in the Arab Republic of Egypt.The study population included poultry companies that own automated slaughterhouses in the Arab Republic of Egypt.Survey forms were distributed to obtain the primary data related to the variables of the study to managers, heads of departments, supervisors and employees in (departments / departments of supply chains / logistics, procurement, stores or logistics) or their equivalent in the companies under study, and they were chosen because they are in charge of managing supply chain activities in The companies under study.The results of the study: The study concluded that there is a direct (positive) correlation with a statistical significance between the dimensions of supply chains and the achievement of competitive advantage for poultry production companies in Egypt.The study made several recommendations, the most important of which are: Poultry companies should pay attention to supply chain management in its various stages, due to its direct impact on the competitive advantage of the organization, as well as activating control over all supply chain operations and activities.